Integrasi Nilai-Nilai Islam dalam Desain Pembelajaran PAI melalui Identifikasi Karakteristik Peserta Didik - Kelvi Anggraini; Wardi Yansyah Efendi; Gusmaneli Gusmaneli (CV.ITTC INDONESIA, 2025)
This study examines the integration of Islamic values ​​into Islamic Religious Education (PAI) learning design as an effort to shape the character and spirituality of students holistically. The integration of Islamic values ​​is not only achieved through the addition of verses or hadith, but also through the internalization of moral, social, and spiritual values ​​in all learning components. The study highlights the importance of recognizing student characteristics as a basis for designing learning strategies tailored to their cognitive, emotional, and spiritual needs. The strategies implemented include Contextual Teaching and Learning (CTL), Project-Based Learning (PjBL), Problem-Based Learning (PBL), role models, and the use of digital technology relevant to the modern era. Evaluation of the effectiveness of Islamic value integration is conducted through authentic observation, portfolios, and self-assessment to assess the holistic internalization of values. The results indicate that PAI learning design based on the integration of Islamic values ​​can improve students' religious understanding, Islamic character, and spiritual awareness in the context of madrasah education.